Differences in Foreign Language Choice of Students from Different Social Backgrounds - Sebestyén, Krisztina (Central European Journal of Educational Research, 2021)
According to previous research (e.g. Bernstein, 1971; Gogolin, 2014; Hegedűs et al., 2019), family background plays a decisive role in an individual's mother tongue acquisition and in learning foreign languages. In another study, parents with a high social background (54.0%) chose German for their children, and parents with a low social background (56.9%) chose English in primary school (Sebestyén, 2021). Based on this, in the study I examine what difference can be detected in the foreign language choice of high school students from different social backgrounds. In the study, I analyze the student data (890 people) of my database entitled “German learning and teaching in Hajdú-Bihar and Szabolcs-Szatmár-Bereg counties” prepared in the 2018/2019 school year, during which I perform cross-tabulation and cluster analysis with the help of SPSS program. The database contains data on 11th grade high school and vocational high school students who studied German and / or English in high school. As the results, there are differences between the learned foreign languages among secondary school students according to family background. Among the clusters related to high school choice, those belonging to the “Higher Education Oriented Local” cluster are most interested in foreign languages, most German-speaking (74.0%) and English (89,0%) students tend to be in this cluster. Overall, the majority of respondents learn English, while students from higher social backgrounds (also) learn German.